2010
DOI: 10.1002/app.32166
|View full text |Cite
|
Sign up to set email alerts
|

Co(III) complex mediated microwave‐assisted synthesis of PAN

Abstract: Free radical polymerization of acrylonitrile (AN) is efficiently, easily, and quickly achieved in the presence of Co(III) complex, [Co(III) en 3 ]Cl 3 and ammonium persulphate (APS) in domestic microwave oven. The rate of polymerization depends on the power and time of microwave irradiation, and is independent of the technique employed (periodic or continuous irradiation). The conversion of monomer to the polymer was mostly excellent in gram scale. Irradiation at low power and time produced more homogeneous po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…As illustrated from chromatographic results, M n of dominant fraction is located around 950 and 1500 for PIn synthesized conventionally using APS and KIO 3 , respectively [as shown in Figure 5(a,b)], while 1450 and 1550 for PIn synthesized by APS and KIO 3 via microwave radiation, respectively [as shown in Figure 5(c,d)]. Sharp peaks are observed for PIn obtained using oxidizing agent KIO 3 indicating a narrow distribution of M n while the minuscule humps present for PIn obtained using oxidizing agent APS (as shown in inset of Figure 5) are due to fragmentation of polymeric chains and traces of lower molecular weight polymeric fragments (i.e.…”
Section: Molecular Weight Determinationmentioning
confidence: 98%
See 2 more Smart Citations
“…As illustrated from chromatographic results, M n of dominant fraction is located around 950 and 1500 for PIn synthesized conventionally using APS and KIO 3 , respectively [as shown in Figure 5(a,b)], while 1450 and 1550 for PIn synthesized by APS and KIO 3 via microwave radiation, respectively [as shown in Figure 5(c,d)]. Sharp peaks are observed for PIn obtained using oxidizing agent KIO 3 indicating a narrow distribution of M n while the minuscule humps present for PIn obtained using oxidizing agent APS (as shown in inset of Figure 5) are due to fragmentation of polymeric chains and traces of lower molecular weight polymeric fragments (i.e.…”
Section: Molecular Weight Determinationmentioning
confidence: 98%
“…This is due to wide range molecular weight distribution of PIn synthesized by APS in which the longer polymeric chains may be grasped together by smaller chains. That is why PIn synthesized by APS shows degradation of about 67% at 600 C whereas PIn synthesized by KIO 3 shows same degradation at 340 C. Thermal behavior of PIns is also analyzed by DTA (as is shown in Supporting Information Figure S1). From this study we observed that degradation of PIns is exothermic in nature from 100 C to 600 C.…”
Section: Molecular Weight Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to systematically study the interaction of P(AN-co-NVP)-based nanoparticles with ECs, monomodal, narrow particle size distributions were envisioned, which ideally should be formed by combining copolymer synthesis and particle formation in an integrated process. The synthesis of AN-based nanoparticles has been systematically studied, mostly based on (macro)emulsion/dispersion polymerization [18][19][20], which in some cases involved the use of solvents or metal based catalysts with assumed toxicity and/or may result in particles with a larger size distribution. Several of these challenges can be overcome by acrylonitrile copolymerization in miniemulsions [21], in which less surfactant is required when compared to the high detergent levels used for polyacrylonitrile nanoparticle synthesis in microemulsions [22] and a hydrophobic costabilizer impedes Ostwald ripening of nascent droplets/particles, thereby enabling narrow size distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Free radical polymerization of acrylonitrile (AN) is efficiently, easily, and quickly achieved in the presence of Co(III) complex, [Co(III) en 3 ]Cl 3 and ammonium persulphate (APS) in domestic microwave ovens. Irradiation at low power and time produced more homogeneous polymers with high molecular weight and low polydispersity in comparison to the polymer formed by conventional heating method [52].…”
Section: Free Radical Homopolymerizationmentioning
confidence: 99%